TEACHING IRREGULAR VERBS THROUGH DRILL TECHNIQUE - Eka Agustina (Channing : Journal of English Language Education and Literature, 2017)
This study aimed at finding out whether or not drill tenhnique influence the students’ irregular verbs of SMA Negeri 1 Buay Madang OKU Timur. The population of this study was 195 students of SMA Negeri 1 Buay Madang OKU Timur. From the population, there were 40 students taken as sample of experimental group and 40 students were as control group. The sample was taken using cluster random sampling. In carrying out the research, the writer used match t-test for analizing the data. The result of this research show that drill technique is effective to teach irregular verbs at the tenth year students of SMA Negeri 1 Buay Madang.